Study the effect of urokinase-type plasminogen activator (UPA) and some biochemical parameters in Iraqi hemodialysis patients with type 2 diabetes - Fatima Ali Essa Al-Sudani; Nawal Mohammed Jawad Al-Shammaa (Medical Journal of Babylon)
Abstract The most common cause of end-stage renal disease (ESRD) and leading ultimately to hemodialysis (HD) is type 2 diabetes mellitus (T2DM). The current study aims to assess the role of serum urokinase plasminogen activator (UPA) levels among Iraqi hemodialysis patients with ESRD with type 2 diabetes. The study encompassed 50 patients aged 40–74 years (35 males and 15 females), admitted to the Iraqi dialysis center at Baghdad Teaching Hospital, Al-Hayat Center at Al-Karama Teaching Hospital, and Hamida Al-Misfah Dialysis Center in Imam Al-Kadhimin Medical City for the period from October 2022 to February 2023. Were diagnosed based on previous medical reports, and laboratory tests by a consultant nephrologist. UPA, Blood. Urea, Creatinine, fasting serum glucose (FSG), HbA1c, Insulin, HOMA-IR, and lipid profile levels were determined. The present study showed a significant increase in serum UPA levels in HD patients in ESRD with T2DM compared to control. In addition, there was an important negative correlation between UPA and Hb1AC, FSG, and a positive correlation with VLDL-C and TG in HD patients in ESRD with T2DM patients. This study demonstrates increased UPA serum levels in HD in ESRD with T2DM patients and associated with FSG, Hb1AC, TG, and VLDL this shows that it can be considered a good marker for the development of diabetes complications, the most important of which is diabetic kidney disease (DKD).